Navigating Communication Challenges in using English as a Lingua Franca: The Stories of Indonesian Students in Australia - Kurniawan, Hasyim (Lexicon, 2024)
This research explores intercultural communication encountered by Indonesian students studying in Australia, where English serves as the lingua franca. Employing the narrative accounts of participants as a valuable source of qualitative data, this research aims to identify the distinct categories of understanding-related problems experienced by Indonesian students when engaging with non-native speakers of English and to explain the strategies employed in managing such challenges. Additionally, an evaluation of the efficacy of English language teaching and learning in Indonesia is conducted to ascertain its role in mitigating understanding issues. Data for this study were gathered through open-ended interviews conducted with eight Indonesian students enrolled in master's programs at Monash University, Australia. The findings reveal that students encounter three levels of understanding problems: 1) non-understanding, 2) partial understanding, and 3) misunderstanding. The analysis underscores two predominant strategies employed by students in managing these challenges: 1) signaling the problem and 2) allowing it to pass without clarification. Furthermore, the research reveals that although participants find their English studies effective in academic contexts like class discussions and written tests, they feel that their acquired language skills lack adequate guidance for daily interactions in Australia. The study proposes specific improvements in English language teaching (ELT) in Indonesia to better equip students for the diverse linguistic challenges in intercultural settings by incorporating three competences namely interactional competence, strategic competence and multidialectal competence.